Pengaruh Kepemimpinan Transformasional, Kepuasan Kerja Dan Komitmen Organisasional Terhadap Organizational Citizenship Behavior PT Sinergi - Roby Irzal Maulana* (LPPM Universitas BSI, 2020)
ABSTRACTThe purpose of this study is to determine the effect of transformational leadership, work satisfaction, and organizational commitment of organizational citizenship behavior. The study used all employes in PT. Sinergi as population. Sampling technique usedin this study is sensus method. Sample used in this study are 88 employes. Data collection methods used in this study is kuisioner and interview. This study applied multiple linear regression analysis with SPSS 21.0 for windows. The analysis shows that transformational leadership, work satisfaction, and organizational commitment has positive and significant effect on financial performance on employes in PT. Sinergi. To improve organizational citizenship behavior, it must pay attention to inspirational motivation, promotion opportunities and commitment afektive.Keywords: transformational leadership, work satisfaction, organizational commitment, organizational citizenship